Case report: MOG-IgG-associated encephalitis with Epstein-Barr virus infection and Alzheimer's pathologic change in cerebrospinal fluid - Li, Lin; Li, Chuan; Yao, Dan; Hao, Yun-feng; Zhao, Chao; Yan, Qi; Liu, Jun-tong; Liu, Shu-yu; Zhu, Wen-ping; Du, Ying; Zhang, Wei (Frontiers in Neurology, 2022)
Immunoglobulin G antibodies to myelin oligodendrocyte glycoprotein (MOG-IgG) associated disease is a rare, demyelinated disease in the central nerve system (CNS) predominately involving optic nerve, spinal cord, and brain leading to optic neuritis (ON), transverse myelitis (TM), encephalitis. The phenotype of MOG-IgG-associated encephalitis is similar to acute disseminated encephalomyelitis (ADEM) presenting with seizures, abnormal behavioral and psychological symptoms, and cognitive impairment. A few brain biopsies show multiple sclerosis (MS) pattern histopathology with T cells, macrophages, and complement activation. To date, how MOG-IgG is produced is unknown. Herein, we report a case of a 32-year-old male with MOG-IgG-associated encephalitis presenting MOG-IgG in cerebrospinal fluid (CSF) but seronegative, as well as Epstein-Barr virus (EBV) infection and Alzheimer's pathologic change in CSF (Aβ42 = 317 pg/ml, T-Tau = 538 pg/ml, p-Tau =10.09 pg/ml). With a combination treatment of administering intravenous immunoglobulin (0.4 mg/kg/d, 5 days) with a low dose of methylprednisolone (80 mg/d, 5 days) and rituximab (100 mg/week, 3 weeks), the patient recovered significantly after 3 months follow-up. This case provides us with new thoughts into the production of MOG-IgG and the possible pathologic mechanism of MOG-IgG-associated disease (MOG-AD) and simultaneously further confirms the interaction between EBV and changes of CSF biomarkers of Alzheimer's disease (AD).